PENGARUH MODAL INTELEKTUAL, PROFITABILITAS DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP NILAI PERUSAHAAN - Alfian Diaz Alfredo, (2021)
This study aims to determine and empirically test the effect of Intellectual Capital, Profitability, and Corporate Social Responsibility Disclosure on Company Value of listed industrial companies in Indonesia Stock Exchange in the 2017 - 2019 period. In this study, the Company Value was measure by Price to Book Value. This study is a type of quantitative research that uses secondary data based on annual reports. A sample of this research consisted of 30 industrial companies. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing (t-test ) with Eviews 10. Based on the result of data analysis, it can be concluded that Intellectual Capital and profitability have a significant effect on company value. While corporate social responsibility disclosure has no effect on company value.